Uma análise de plataformas de streaming e as possibilidades de interface para conteúdos sob demanda na TV 3.0 - Montezano, Cristiane Turnes; Pernisa Júnior, Carlos; Moreno, Marcelo F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
This study examines the interfaces of streaming platforms to explore the potential adaptations that the next generation of television, known as TV 3.0, could incorporate through the integration of OTA (over-the-air) and OTT (over-the-top) content. The envisioned future of television promises a seamless blend of traditional broadcast signals with internet-based services, paving the way for the integration of on-demand content within this new TV standard. In light of this evolution, a significant opportunity arises to develop an advanced interface for navigating and selecting on-demand content, referred to as the Electronic Content Guide (ECG). This paper presents a detailed analysis of several streaming platforms, concentrating on their interfaces, which demonstrate features that align with the anticipated characteristics of TV 3.0, namely the provision of on-demand content alongside live broadcasts. The research methodology begins with an exploratory literature review, followed by a comprehensive examination of these platforms. This paper is part of a broader research initiative, which will be expanded upon in subsequent publications. The primary objective is to investigate the possibilities for content organization on screen and the resulting interactions that will shape the interface of TV 3.0.